Investigating effectiveness of early reading intiative in Malisa central cluster in Silobela - Mutanda, Shumbei (Midlands State University, 2020)
The main purpose of this study was to investigate effectiveness of early reading initiative in Malisa Central Cluster in Silobela. The researcher used a qualitative approach. The sample comprised infant teachers from seven rural schools. The data collection tools were the questionnaires. The findings from the study indicated that for the teachers who answered the questionnaire ERI plays a crucial role in language teaching through the use of word picture matching, look and say and phonic method, hence unavoidable in the event of uprooting readership deficiency and skill learners on reading performance. Based on the findings, the study concluded that it may be possible to help establish ERI more firmly in the teaching process by developing a set of specially designed, structured teaching materials for young learners in the preschool and infant department. Recommendations are that parents and sponsors are to be updated on importance of ERI through workshops, more staff development should be done foe ERI implementers, government should make policies on ERI and enforce them in schools, availability of resources is necessary, hence should be budgeted for, modern infrastructure is a necessity as well as establishment of technology in ERI implementation.